Finance Professionals Understanding of Digital Transformation Challenges and Opportunities in Financial Reporting - Rina Destiana (Yayasan Adra Karima Hubbi, 2024)
The financial reporting landscape has changed dramatically as a result of digital transformation. The purpose of this study is to investigate how financial professionals perceive the potential and difficulties brought about by digital transformation in relation to financial reporting. The study, which used a qualitative methodology and in-depth interviews with 30 financial professionals from a range of industry sectors, finds that although digital transformation improves financial reporting accuracy and efficiency, it also presents problems, such as the requirement for more technological know-how and data security. Opportunities for real-time data analysis, process automation, and quicker decision-making are recognized by financial experts. They also draw attention to issues with data protection, the necessity of ongoing education, and modifications to conventional accounting positions. These results offer practitioners, regulators, and educators important information to help them prepare.